The role of diversification in the revenue composition of Italian farms - Roberto Henke; Orlando Cimino; Francesco Vanni (Italian Review of Agricultural Economics (REA), 2022)
The main aim of this paper is to analyse the evolution, patterns and models of revenue diversification in Italian agriculture in different contexts and for different typologies of farms. The analysis is based on the calculation of the inverse of Herfindahl index, by using different variables available in the Italian FADN database (years 2008, 2013 and 2018), followed by a multiple regression model to analyse the relationship between the diversification index and other variables, in order to highlight both the internal and external factors affecting on-farm diversification processes. The article shows that Italian farms have increasingly adopted non-agricultural revenue diversification strategies to reduce risk and maximize factors' productivity. Among these, agritourism is by far the most relevant; however, in the last few years the production of renewable energy has been growing relatively rapidly. Overall, the study shows that on-farm diversification activities can be either an opportunity for a new entrepreneurship in agriculture or a survival strategy for small and marginal farms that are not sufficiently integrated in the national agri-food system.
Keywords: Q12; 330; farm revenues; on-farm diversification; FADN; Herfindahl index